Sistem Informasi Pemesanan Menu Kafe Menggunakan QR-Code - Andrian Eko Widodo; Fanny Fatma Wati; Aprih Widayanto (J-INTECH ( Journal of Information and Technology), 2023)
During this pandemic, to reduce the spread of COVID-19, it is necessary to implement health protocols in community activities, including in the culinary business. By utilizing the QR-Code the cafe owner can realize the use of a digital menu that can be accessed from a cafe visitor's smart device. The use of digital menu lists is intended to prevent Covid-19 transmission through manual lists or menu books, which are usually used interchangeably by many visitors. By scanning the QR-Code placed on the cafe table, visitors can select a menu and place an order by minimizing contact with manual menu lists and cafe employees. Through this application, cafe owners can also manage sales at their cafes, including sales statistics, receipt printing, menu updates, etc.